Judicial rulings and political narratives: Analyzing the impact of Roe v. Wade's overturning on digital discourse using machine learning - Nikolina Klatt (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2024)
How do judicial decisions influence political discourse, particularly in areas as contentious as abortion rights? This study investigates how the overturning of Roe v. Wade affected the narrative strategies of U.S. representatives on social media, focusing on variations by party affiliation and geography. While there is literature on the influence of judicial decisions on public opinion and policy, the effect on political narratives remains underexplored. To address this gap, the study analyzes 5,293 tweets from U.S. representatives in 2022 by supervised text classification and statistical modeling to identify shifts in narrative strategies. The study found the leaked opinion draft acted as a catalyst, which prompted an increase in stories of decline-narratives that emphasize a worsening situation-particularly for Republicans. This study provides empirical evidence of how political narratives evolve in response to landmark judicial changes and insights into the strategic use of narratives by political actors in digital communication.
Keywords: 320